Trade Reform Under Partial Currency Convertibility : Some Suggestive Results. (IMF Working Papers; Working Paper, 1988)
This paper discusses the macroeconomic implications of trade reform in the presence of capital account restrictions. The latter is modelled by recognizing prior constraints on free currency convertibility that are imposed via the use of a multiple exchange rate system. The results of the analysis indicate that the preferred sequence of liberalization need not be of the commonly advocated 'current account first' variety, and that real depreciation rather than real appreciation is in fact a more probable outcome following domestic tariff liberalization.